Antibiotic Resistance Profile, Outer Membrane Proteins, Virulence Factors and Genome Sequence Analysis Reveal Clinical Isolates of Enterobacter Are Potential Pathogens Compared to Environmental Isolates - Mishra, Mitali; Panda, Sasmita; Barik, Susmita; Sarkar, Arup; Singh, Durg Vijai; Mohapatra, Harapriya (Frontiers in Cellular and Infection Microbiology, 2020)
Outer membrane proteins (OMPs) of gram-negative bacteria play an important role in mediating antibacterial resistance, bacterial virulence and thus affect pathogenic ability of the bacteria. Over the years, prevalence of environmental antibiotic resistant organisms, their transmission to clinics and ability to transfer resistance genes, have been studied extensively. Nevertheless, how successful environmental bacteria can be in establishing as pathogenic bacteria under clinical setting, is less addressed. In the present study, we utilized an integrated approach of investigating the antibiotic resistance profile, presence of outer membrane proteins and virulence factors to understand extent of threat posed due to multidrug resistant environmental Enterobacter isolates. Also, we investigated clinical Enterobacter isolates and compared the results thereof. Results of the study showed that multidrug resistant environmental Enterobacter isolates lacked OmpC, lacked cell invasion abilities and exhibited low reactive oxygen species (ROS) production in neutrophils. In contrast, clinical isolates possessed OmpF, exhibited high invasive and adhesive property and produced higher amounts of ROS in neutrophils. These attributes indicated limited pathogenic potential of environmental Enterobacter isolates. Informations obtained from whole genome sequence of two representative bacterial isolates from environment (DL4.3) and clinical sources (EspIMS6) corroborated well with the observed results. Findings of the present study are significant as it highlights limited fitness of multidrug resistant environmental Enterobacter isolates.